Bleximenib, the novel menin-KMT2A inhibitor JNJ-75276617, impairs long-term proliferation and immune evasion in acute myeloid leukemia - Shanna M. Hogeling; Duy Minh Lê; Nikita La Rose; Min Chul Kwon; Albertus T.J. Wierenga; Fiona A.J. van den Heuvel; Vincent van den Boom; Anna Kuchnio; Ulrike Philippar; Gerwin Huls; Jan Jacob Schuringa (Haematologica)
Acute myeloid leukemia (AML) remains challenging to treat, which in part relates to genetic heterogeneity of the disease, to the protective tumor microenvironment driving resistance to therapy, and also to immune evasion characteristics of leukemic cells. Targeting epigenetic programs in AML provides an attractive opportunity to impair long-term proliferation and induce differentiation. The novel inhibitor JNJ- 75276617 (bleximenib) targets the menin-KMT2A interaction and provides preclinical efficacy in AML (Kwon et al1). Here, we provide mechanistic insight in how JNJ- 75276617 impairs proliferation and drives differentiation of primary AML patient cells. A large-scale drug screen was set up in which genetic alterations and quantitative proteomics were compared with drug sensitivity in a preclinical setting, which revealed that granulocyte macrophage progenitor (GMP)-like AMLs display the greatest sensitivity. Furthermore, we identified that NPM1c/DNMT3Amut AMLs are sensitive, and some NPM1wt AML subtypes without KMT2A-MLLT3 rearrangements benefit from menin-KMT2A inhibition. Genome-wide ChIP-seq studies revealed patient-specific epigenetic alterations upon JNJ-75276617 treatment, uncovering a striking upregulation of MHC class I and class II expression as a consequence of epigenetic changes upon menin-KMT2A inhibition, independent of MEIS1 loss but involving CIITA activation. Functionally, this results in enhanced sensitivity of leukemic blasts to T cell-mediated cytotoxicity in allogeneic and autologous settings. Our data indicate that JNJ-75276617 provides a potential therapeutic approach whereby not only proliferation is impaired and differentiation is induced, but whereby therapeutic benefit might also be achieved by reactivating the antigen presentation machinery.